Gut dysbiosis is associated with difficult-to-treat rheumatoid arthritis - Patricia Ruiz-Limón; Patricia Ruiz-Limón; Patricia Ruiz-Limón; Natalia Mena-Vázquez; Natalia Mena-Vázquez; Isabel Moreno-Indias; Isabel Moreno-Indias; Isabel Moreno-Indias; Jose Manuel Lisbona-Montañez; Jose Manuel Lisbona-Montañez; Jose Manuel Lisbona-Montañez; Arkaitz Mucientes; et al. (Frontiers in Medicine)
BackgroundDifficult-to-treat rheumatoid arthritis (D2T RA) refers to a subset of patients who fail to achieve adequate disease control after the use of two or more biological or targeted synthetic disease-modifying antirheumatic drugs (b/tsDMARDs) with different mechanisms of action, while maintaining active inflammatory disease. This presents a therapeutic challenge and highlights the need to explore contributing factors such as the potential role of the gut microbiota. Therefore, the aim of this study was to analyze the gut microbiota and inflammation in patients with D2T RA in comparison to patients with easy-to-treat RA (E2T RA).ObjectiveTo analyze the gut microbiota and inflammation in patients with D2T RA.MethodsWe performed an observational study of a prospective cohort between 2007 and 2011 and analyzed the gut microbiota. In 2022, we identified 2 extreme patient phenotypes: (1) D2T RA, which was defined as failure of ≥2 biological or targeted synthetic disease-modifying antirheumatic drugs (b/tsDMARDs) (with different mechanisms of action) plus signs of active disease; and (2) easy-to-treat RA (E2T RA), i.e., stable disease managed with a single treatment. The gut microbiota was analyzed using 16S rRNA gene sequencing; bioinformatics analysis was performed using QIIME2, and its functionality was inferred through PICRUSt. We recorded data on clinical findings, inflammation, and cytokines. A Cox multivariate analysis was performed to identify factors related to D2T RA.ResultsThe study population comprised 39 patients: 13 (33%) with D2T RA and 26 (66%) with E2T RA. The families Lachnospiraceae and Pasteurellaceae, and their genera Coprococcus and Haemophilus were more abundant in E2T RA patients, while the genus Megasphaera was more abundant in D2T RA patients. The Firmicutes/Bacteroidetes ratio decreased in D2T RA patients. The metabolic profile of the gut microbiota was characterized by differences in Degradation/Utilization/Assimilation pathway and the Biosynthesis pathway. The factors associated with D2T RA were inflammatory activity according to DAS28-ESR (HR, 2.649; p = 0.013), prednisone (HR, 3.794; p = 0.008), and the Firmicutes/Bacteroidetes ratio (HR, 0.288; p = 0.033).ConclusionThe composition of the gut microbiota of patients with D2T RA differed from that of E2T RA patients, as did the metabolic pathways.